Desarrollo de un prototipo para potabilización de agua alimentado por energía limpia, que brinde el recurso hídrico a comunidades que no hace parte de la red de agua potable, caso recinto tazones, provincia de Esmeraldas - Yánez Díaz, Sergio André (2021)
This thesis Report Piece of work focuses on the development of a proposal for a water filtration prototype in a rural area in the province of Esmeraldas in Ecuador. This proposal addresses social aspects such as the lack of drinking water in rural areas of the country, the lack of commitment from government entities to meet the need for water resources in a province that is surrounded by water, as well as different systems of filtering, ways of transporting water without impact by weight, ways of collecting water, energy based on sunlight, among other technical aspects…